2021
DOI: 10.1371/journal.pone.0255251
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of mental health problems before and after easing COVID-19 restrictions: Evidence from a 105248-subject survey in general population in China

Abstract: Background The COVID-19 pandemic has alarming implications for individual and population level mental health. Although the future of COVID-19 is unknown at present, more countries or regions start to ease restrictions. The findings from this study have provided the empirical evidence of prevalence and patterns of mental disorders in Chinese general population before and after easing most COVID-19 restrictions, and information of the factors associated with these patterns. Methods A cross-sectional population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Similar findings have been shown internationally. A large population-based survey study in China (N = 105,248) found that the prevalence of being high risk for mental disorders decreased from 25.8% when lockdown restrictions were in place (early-February 2020) to 20.9% when most COVID-19 restrictions were eased (mid-March 2020) [43]. However, it is still unknown whether this 'bounce-back' effect is present across all population sub-groups, or whether the mental health of certain groups remain negatively impacted by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been shown internationally. A large population-based survey study in China (N = 105,248) found that the prevalence of being high risk for mental disorders decreased from 25.8% when lockdown restrictions were in place (early-February 2020) to 20.9% when most COVID-19 restrictions were eased (mid-March 2020) [43]. However, it is still unknown whether this 'bounce-back' effect is present across all population sub-groups, or whether the mental health of certain groups remain negatively impacted by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of current mental health disturbances found in this study, at 49.1%, was comparable to that in previous studies. In Jordanian medical schools, half of the participants had severe mental disorders, and only 13.2% were likely to be well (26); In Turkey, among 1375 medical students, 52.4% of them reported feeling mentally unwell (27); and a study in India showed that nearly half of 2,021 medical students reported some degree of mental health problems, such as depression (50.27%), anxiety (51.46%), and stress (41.61%) [ 35 ]. Meanwhile, most students in this study had a moderate degree of depression (35.3%), followed by moderately severe depression (31.7%).…”
Section: Discussionmentioning
confidence: 99%
“…One particular limitation is the lack of a control group. People not infected by SARS-CoV-2 have also experienced fatigue and psychological issues during the pandemic [ 12 , 13 ]. However, most of these symptoms can be expected to decrease as any remaining restrictions are lifted [ 13 ], and we therefore believe that our results represent the long-term effects of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…People not infected by SARS-CoV-2 have also experienced fatigue and psychological issues during the pandemic [ 12 , 13 ]. However, most of these symptoms can be expected to decrease as any remaining restrictions are lifted [ 13 ], and we therefore believe that our results represent the long-term effects of COVID-19. A further limitation is that we only included cognitive symptoms such as concentration and memory difficulties at follow-up.…”
Section: Discussionmentioning
confidence: 99%